Restaurações provisórias contemporâneas: efeito do tempo e meios de imersão nas propriedades físico-mecânicas - Jorge, Caroline de Freitas [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Different materials are used to confection of the provisional restorations. With advance technology computer-aided design was possible to develop new materials, such as Computer-Aided Design/Computer-Aided Manufacturing - CAD/CAM. This way, the objective of this present study is to evaluate sorption (SR), solubility (SO) surface roughness (Ra) and Knoop microhardness (MK) of the pre-fabricated polymer blocks or high density polymer to CAD/CAM comparing with different materials (thermo polymerized acrylic resin, auto polymerized acrylic resin and bisacrylic resin), after immersion in acid-color solutions, in the periods of 7,14, 28, 90 and 180 days. It Were made 160 specimens with 10×10×3 (±0,005mm), divided in 16 groups (n=10) according the material and solution. Four different resin were evaluated: RAT - thermo polymerized acrylic resin (Clássico), RAA - auto polymerized acrylic resin (Alike), RB - nanoparticulate bisacrylic resin (Protemp4) and RCAD - pre-fabricated polymer blocks (PMMA) to CAD/CAM system (Telio CAD); immersed in following solutions: artificial saliva (S- Control), cola soft drink (R), coffee (C) and red wine (V). Knoop microhardness, surface roughness, sorption and solubility were realized the analyzes in 6 periods (7, 14, 28, 90 e 180 days). The Shapiro-Wilk and Levene method were used to test normality and confirm the homogeneity of the data. ANOVA 3 factors for repeated measurements was used to verify the influence of material type, solution and immersion period. The Bonferroni test was used as a posthoc technique. In the analysis of microhardness after 180 days, the RCAD showed the highest values while the RB presented the lowest values. In the roughness in 180 days, the RAA group presented the highest values (> 0,121), independently of the solution, while the lowest values were found in the RAT (0.063), RB (0.06) and RCAD (0.062) groups when...

Diferentes materiais são usados para a confecção de coroas provisórias. Com avanço da tecnologia de confecção assistida por computador (Computer-Aided Design/Computer-Aided Manufacturing - CAD/CAM), foi possível o desenvolvimento de novos materiais, como os blocos pré-fabricados de polímeros para CAD/CAM. Assim, o objetivo desse estudo foi avaliar o comportamento físico-mecânico, por meio da análise da microdureza Knoop, rugosidade superficial, sorção e solubilidade dos blocos pré-fabricados para CAD/CAM, comparando com diferentes materiais (resina acrílica autopolimerizável, resina acrílica termopolimerizável e resina bisacrílica), após imersão em soluções ácidas/corantes, nos períodos de 7, 14, 28, 90 e 180 dias. Foram confeccionados 160 espécimes (10×10×3 (±0.005) mm), 40 de resina acrílica termopolimerizável (RAT), 40 de resina acrílica autopolimerizável (RAA), 40 de resina bisacrílica (RB) e 40 de blocos pré-fabricados para CAD/CAM (RCAD). Os espécimes foram imersos em saliva artificial (SA), refrigerante de cola (CO), café (CA) e vinho (V). Foram realizadas as análises da microdureza Knoop, rugosidade superficial, sorção e solubilidade em 6 períodos (0, 7, 14, 28, 90 e 180 dias). O método Shapiro-Wilk e Levene foram usados para testar a normalidade e confirmar a homogeneidade dos dados. ANOVA 3 fatores para medidas repetidas foi usada verificar a influência do tipo de material, solução e período de imersão. O teste de Bonferroni foi utilizado como técnica posthoc. Na análise de microdureza após 180 dias, o RCAD apresentou os maiores valores enquanto o RB apresentou os menores. Já na rugosidade em 180 dias, o grupo RAA apresentou os maiores valores (>0,121), independentemente da solução, enquanto os menores valores foram encontrados nos grupos...
Keywords: Resinas acrílicas; Projeto auxiliado por computador; Coroa dentária; Acrylic resins